The nutritional ecology of maturation in a carnivorous insect. (17th October 2018) - Al Shareefi, Ekhlas; Cotter, Sheena C
Abstract : Protein or fat? A carnivore's priorities change with age. Immature beetles target protein while mature beetles watch their weight. We tested how the feeding behavior of beetles changes as they become reproductively mature by restricting them to diets that did not provide their preferred ratio of proteins to fats. Mature beetles consumed the same calories across diets but young beetles tried to maintain protein intake, even on low-protein diets, resulting in obesity. Abstract: Herbivores and omnivores, faced with a nutritionally complex diet, have evolved the capacity to balance the intake of specific nutrients. Recent studies have found that carnivores also have this capacity, despite their more nutritionally homogeneous diet. However, unlike herbivores and omnivores who prioritize protein intake when restricted to imbalanced foods, carnivores instead show much stricter regulation of fat intake. These choices to over- or under-consume nutrients when the intake target cannot be achieved are known as rules of compromise . To date, studies examining these rules have all been carried out at a single life stage, and it is unclear if these rules regarding the prioritization of nutrients are fixed or labile. We address this question with a carnivorous beetle, Nicrophorus vespilloides . We use a combination of dietary restriction and choice tests to determine the intake target and rules of compromise in reproductively mature beetles and in newly emerged adults undergoing a period of maturation feeding. We show that, despite having very similar intake targets, the rules of compromise differ between the 2 life stages. Although mature adults follow the typical carnivore rule of fat prioritization, immature adults behave more like omnivores, showing strict regulation of protein intake, resulting in obesity when restricted to protein-poor diets. These alternate rules suggest different mechanisms or capacities to cope with excess protein across these life stages. Examining how intake targets and rules of compromise change across life stages could be a valuable approach for our understanding of how animals will fare under rapidly changing environmental conditions.